Peran Edukasi Orang Tua Dalam Implementasi Baby Gym Terhadap Pertumbuhan Dan Perkembangan Bayi - Sri Sundari; Inas Gita Amalia; Elin Wijaya; Oktaviana Maharani (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Introduction: Infant growth and development are important aspects of early life that are Influenced by stimulation and the active role of parents. One effective form of stimulation in supporting infant development is baby gym, a structured movement exercise designed to stimulate motor skills, coordination, and sensory responses through enjoyable physical activities. This study aimed to evaluate the role of parental education in the implementation of baby gym and its impact on infant growth and development in Mrisi Hamlet, Bantul. Methods: This study employed a pre-test and post-test design with a control group. A total of 40 infants aged 6–12 months were randomly assigned into two groups: the intervention group receiving education about baby gym (n = 20) and the control group (n = 20). The educational intervention was conducted over six weeks and included baby gym techniques as well as guidelines for home implementation. Measurements included body weight, body length, and motor and cognitive development using the Developmental Pre-Screening Questionnaire (KPSP). Results: The analysis showed significant improvements in the intervention group compared to the control group. The average increase in body weight was 1.4 kg (p = 0.004; p < 0.05), and body length increased by 3.9 cm (p = 0.0002; p < 0.001). Motor development improved significantly (p = 0.0001; p < 0.001), while cognitive development increased by 8.3 points (p = 0.001; p < 0.01). Overall, the group receiving education demonstrated significant improvements in all aspects of infant growth and development (p < 0.01). Conclusion: Parental education regarding baby gym has been proven effective in improving infant growth and development, both physically and cognitively. These findings emphasize the importance of empowering parents through education to optimize the benefits of baby gym in supporting comprehensive infant growth and development.